(untitled) (CIPEEX, 2026)
Muscle strength is essential for health and functionality, serving as a relevant indicator for daily activities and being associated with the prevention of disabilities. The reduction of strength, especially in the spinal musculature, leads to pain and represents a significant burden on healthcare systems. Objective: To identify and analyze reference values for the strength of lumbar extensor muscles (LEM) in adults, based on a literature review. Method: This is an integrative review aimed at gathering studies that reported reference values for lumbar muscle strength. The search was conducted in the Scopus, National Library of Medicine, SciELO, and Web of Science databases, using keyword blocks related to adults, dynamometry, and reference values. Results: Six studies were included, showing heterogeneity in protocols, populations, and equipment used (isokinetic and portable dynamometers), with substantial variation in strength and torque values. This reveals a gap in the literature as well as the absence of consolidated reference values. Conclusion: Variations in values, as well as in lumbar muscle strength assessment protocols, highlight the need for more robust studies to standardize lumbar strength evaluation methods.